An inflammation classification system using cytokine parameters. (18th September 2020) - Roe, Kevin
Abstract: Inflammation can be created by several different causes, including a blood clot, an immune system disorder, a cancer, an infection, a chemical exposure, a physical injury, or a neurological condition, such as Alzheimer's or depression. In particular, many infections by viral, bacterial, fungal and protozoan pathogens can cause inflammation. Inflammations can have far‐reaching medical consequences, because chronic or frequent inflammation can assist cancers and initiate autoimmune diseases. Determining the cause of an inflammation can be essential for the medical treatment of an individual, and a classification system can be a useful tool to help a diagnosis, confirm a diagnosis and to determine the most appropriate treatment. However, at present there is no classification system for the different causes of inflammation. This paper describes a classification system that uses seven distinct cytokine parameters to enable the determination of the cause of an inflammation. This classification system is expandable, and it can help determine whether an inflammation is caused by an ischaemia, an immune system disorder, a cancer, an infection, a chemical, a physical injury, or a neurological condition. In some cases, this classification system can help enable a quick primary or secondary determination of an urgent medical emergency when other medical diagnostic resources are unavailable.